Exploring the meaning of a new assistive technology device for older individuals. (November 2014) - Gramstad, Astrid; Storli, Sissel Lisa; Hamran, Torunn
Abstract Researching the outcomes of assistive technology devices (ATDs) for older clients is important to facilitate clinical decision-making. However, to understand the outcomes associated with ATDs, one must investigate the users' experiences and acknowledge the user as an active participant in diverse social contexts. Purpose: To enhance understanding of the users' perspective regarding ATDs, this study aimed to investigate the meaning of the ATD for older individuals still living in their home environment. Methods: To provide descriptions of ATD experiences, older individuals who received a new ATD to compensate for their challenges in moving around, assist in self-care or both were recruited for the study. Participants were interviewed twice, with a few months between interviews, about their experience in using their new ATD. The interview transcripts were analyzed in a hermeneutical–phenomenological research approach. Results: The analysis revealed three recurring themes associated with the description of ATD experiences: "enabling performance and choice", "transformation from requiring assistance to assisting others", and "preparing for the future". Conclusion: The results show that ATDs are used to enhance competence, mastery, control, self-worth, hope, and preparedness. The ATD service delivery should be client-centered and the client should be acknowledged as an active participant in producing change. Implications for Rehabilitation Researching outcomes of assistive technology devices are complicated and should involve the user experience. Assistive technology devices does not have to be used in concrete actions to involve meaning for the user. Health care professionals should be sensitive towards the meaning dimensions of the assistive technology devices as experienced by the user throughout the service delivery process.